ROLE OF INTRINSIC AND EXTRINSIC EPIDEMIOLOGICAL FACTORS ON STRONGYLOSIS IN HORSES - K. Saeed; Z. Qadir; K. Ashraf; N. Ahmad (Journal of Animal and Plant Sciences, 2010)
A total of 133 (65.51%) faecal samples were found positive for various helminths and most frequently strongyle infections were diagnosed with an infection rate of 58.5% (117/200) in a year long study to asses various epidemiological factors influencing the gastro-intestinal nematodes of horses.  Significant difference in the prevalence of various gastrointestinal helminths was detected in the study population (p ≤ 0.05). Species identified included: Parascaris equorum (P. equorum), Dictyocalus arnifieldi (D. arnifieldi), Anoplocephla species, Gastrodiscus aegypticus (G. aegypticus), Strongyloides westeri (S. westeri), Trichstrongylus axei (T. axei), Strongylus vulgaris (S. vulgaris), Strongylus edentatus (S. edentatus), Strongylus equinus (S. equinus) and Trichonema spp. Prevalence of strongylosis was not affected by age (p = 0.1). Higher eggs per gram of faeces (epg) were recorded in young horse (≤ 3 year old horses) as compared with older horses (p ≤ 0.001). Similarly no difference in the prevalence of strongyle infections as influenced by sex could be detected (p = 0.7) and excretion of eggs was also not affected by the sex of the animals (p = 0.06). Season has no impact on the prevalence of strongyle infections (p = 0.07) but shedding intensity of strongyle eggs is affected by season (p ≤ 0.001) and significantly higher egg excretion was recorded in spring and summer.
Keywords: Horses; epidemiology; helminths; strongylosis; epg